Numerical evaluation of methanol synthesis in catalytic wall-coated microreactors: scale-up and performance analysis of planar and monolithic designs - Silva, João Lameu da; Santana, Harrson Silva; Hodapp, Maximilian Joachim (Frontiers in Chemical Engineering, 2024)
Methanol is one of the most important primary chemical compounds, being an interesting alternative for portable energy applications and also acting as a molecular platform for the synthesis of a wide range of commodities and high-added-value products. Traditionally, methanol is obtained by catalytic hydrogenation using synthesis gas (CO/CO2/H2) in fixed-bed reactors (FBRs), which require large reaction volumes and are limited by heat and mass transfer. Wall-coated microreactor technology (MRT) offers a promising alternative to traditional fixed-bed reactors. Despite their potential, industrial-scale adoption of microreactors faces challenges related to scale-up. This article aimed to assess methanol synthesis in wall-coated microreactors (planar, or MRP, and monolithic, or MRM) through numerical performance evaluation, using a fixed-bed reactor as a reference. A pre-analysis of carbon conversion into methanol from experimental data provided insightful conclusions about recommended operating parameters, suggested as 50 bar, 250°C, a CO2 ratio of 0.3–0.4, a gas hourly space velocity (GHSV) of 6,000–8,000 mL/g.h, and a stoichiometric hydrogen/carbon ratio of 2–4. The numerical model, coupling chemical kinetics into fluid dynamics, demonstrated good agreement with experimental data. Subsequently, a design of experiments identified optimal operating conditions for methanol synthesis (250°C, 50 bar, CO2 ratio = 0.32, GHSV = 7,595 mL/g.h, hydrogen/carbon ratio = 2.4) in an FBR. The MRP and MRM presented equivalent performance with the FBR after adjusting the surface catalytic loading. In particular, the MRP showed a potential feature for scale-up due to the decreased pressure drop. A reactor block with 10 parallelized channels was designed and evaluated by changing GHSV between 5,000 and 50,000 mL/g.h and varying surface catalytic loading from 0.04 to 0.12 kg/m2. Despite the formation of recirculation zones in the conical region, the flow distribution remained satisfactory, ensuring virtually uniform methanol production among units, providing increased operational flow, and maintaining the microscale efficiency with a relatively low pressure drop. The present article provides a comprehensive analysis of the fundamental interplay between kinetic effects, mass transfer phenomena, and reactor design in methanol synthesis by applying MRT concepts, offering important insights for performance optimization and scale-up of wall-coated microreactors.